The Utilization of Fermented Kepok Banana Peels on Feed Againts The Percentage of Non Carcass of Local Male Sheep - Zulfahmi (Talenta Publisher, 2019)
This research aims to determine the effects of fermented kepok banana peel as feed by EM4 against the percentage of male local sheep non carcass. This research was conducted in Praditya Rahardja’s Farm, Jalan Bunga Rinte, Kecamatan Medan Tuntungan, Kota Medan from Jully to October 2019. The design used was a completely randomized design (CRD) with 4 treatments and 5 replications so that 20 experimental units. While the sheep were cut for parameter of non carcass as much as 2 from each treatment to produce 8 sheep. The treatments given are P0 (40% kepok banana peel without fermentation in feed), P1 (20% fermented of kepok banana peel in feed), P2 (40% fermented of kepok banana peel in feed), and P3 (60 % fermented of kepok banana peel in feed). The parameters used were percentage of head weight without skin, feet without skin, skin, tail without skin, trachea and lungs, heart, liver, blood, intestine and compound stomach male local sheep. The result showed that the utilization of fermented kepok banana peel as feed for local sheep had no signoificant effect on percentage of weight the head without skin, feet without skin, skin, tail without skin, trachea and lungs, hearts, and liver. But had significant effect on percentage of weight the blood, intestine, and compound stomach male local sheep.